Selenium and Platinum Compounds in Cancer Therapy: Potentiality of their Progeny as Future Chemotherapeutics - Priyadarsini, Karirayani I.; Jain, Vimal Kumar (Current Chemical Biology, 2022)
Compounds based on two different elements, selenium and platinum, have been attracting researchers to deploy them in chemotherapy of human cancers. Selenium, as a micronutrient, plays many important roles in human biology. Different research groups have been developing both inorganic and organoselenium compounds for potential use in the treatment of diseases, including cancer. New synthetic designs are emerging to develop selenium compounds either as chemopreventive or chemotherapeutic agents. Platinum is another important element in cancer therapy. Platinum-based drugs are the first line of treatment for many cancers. Attracted by the fact that chalcogens are excellent ligands for platinum, new ideas are emerging to develop selenium-bound platinum compounds as cancer therapeutics. In this direction, our group has made an effort to develop stable seleno-platinum compounds to explore their anti-cancer potential.
Keywords: radioprotectors